10.0k views
2 votes
Rewrite the function by completing the square
f(x)=x^2-14x+63

User Shabnam
by
4.6k points

1 Answer

3 votes

Answer:

f(x) = (x - 7)² - 14

General Formulas and Concepts:

Pre-Algebra

  • Equality Properties

Algebra I

  • Standard Form: ax² + bx + c = 0
  • Vertex Form: f(x) = a(bx - c)² + d
  • Completing the Square: (b/2)²

Explanation:

Step 1: Define

f(x) = x² - 14x + 63

Step 2: Rewrite

  1. Separate: f(x) = (x² - 14x) + 63
  2. Complete the Square: f(x) = (x² - 14x + 49) + 63 - 49
  3. Simplify: f(x) = (x - 7)² - 14
User Ewooycom
by
5.0k points